Keterkaitan Antara Pendidikan Agama Islam Dengan Pemahaman Konsep Kesehatan Mental Siswa - Akip, Muhamad; Yunus, Muhammad; Sujarwo, Sujarwo (Edification Journal : Pendidikan Agama Islam, 2025)
The purpose of the research is to determine the relationship between Islamic religious education and the concept of student mental health. The research method used in literature study is a qualitative approach. The results of this study show that Islamic Religious Education (PAI) has a significant contribution to students' mental health by introducing religious values that can strengthen their mental and emotional resilience. (1) Emotion Management through Islamic Values (spiritual), patience (patience), gratitude (gratitude), tawakal (surrender to Allah), ikhlas (sincerity), and tazkiyatun nafs (purification of the soul), are very effective in helping students manage emotions (2) The practice of worship as a means of relieving stress such as prayer, dhikr, and prayer has a significant calming effect on the soul. Through worship, students can relieve stress, improve mental well-being, and gain inner peace (3) Islamic Education as a Pillar of Mental Well-being that not only emphasizes the importance of religious understanding, but also teaches about mental health management through positive character development.